The Role and Clinical Implications of the Retinoblastoma (RB)-E2F Pathway in Gastric Cancer - Wu, Tianyi; Wu, Lizhao (Frontiers in Oncology, 2021)
Gastric cancer is the most common malignant tumor in the digestive tract, with very high morbidity and mortality in developing countries. The pathogenesis of gastric cancer is a complex biological process mediated by abnormal regulation of proto-oncogenes and tumor suppressor genes. Although there have been some in-depth studies on gastric cancer at the molecular level, the specific mechanism has not been fully elucidated. RB family proteins (including RB, p130, and p107) are involved in cell cycle regulation, a process that largely depends on members of the E2F gene family that encode transcriptional activators and repressors. In gastric cancer, inactivation of the RB-E2F pathway serves as a core transcriptional mechanism that drives cell cycle progression, and is regulated by cyclins, cyclin-dependent kinases, cyclin-dependent kinase inhibitors, p53, Helicobacter pylori and some other upstream molecules. The E2F proteins are encoded by eight genes (i.e. E2F1 to E2F8), each of which may play a specific role in gastric cancer. Interestingly, a single E2F such as E2F1 can activate or repress transcription, and enhance or inhibit cell proliferation, depending on the cell environment. Thus, the function of the E2F transcription factor family is very complex and needs further exploration. Importantly, the presence of Helicobacter pylori in stomach mucosa may affect the RB and p53 tumor suppressor systems, thereby promoting the occurrence of gastric cancer. This review aims to summarize recent research progress on important roles of the complex RB-E2F signaling network in the development and effective treatment of gastric cancer.